Effects of Sex Hormones in Combined oral Contraceptives and Cyclofem on Female Sexual Dysfunction Score: A Study on Iranian Females - Pazandeh, Farzaneh; Sheikhan, Zohre; Keshavarz, Zohreh; Zahiroddin, Alireza; Dolatian, Mahrokh; Hajian, Sepideh; Khalighi, Tahereh; Kholosi Badr, Farahnaz (Advances in Nursing & Midwifery, 2017)
Abstract Introduction: Unwanted pregnancy can endanger reproductive health, and its complications could adversely affect quality of life in females, families, and the community. A large number of unwanted pregnancies are terminated with abortion or stillbirth. Sex is an important aspect of quality of life. According to reproductive rights, females have the right to experience a safe and enjoyable sexual relationship. This study aimed at comparing sexual function scores between females taking combined oral contraceptives and Cyclofem at health centers affiliated to Shahid Beheshti University of Medical Sciences of Tehran, Iran, During Year 2013. Methods: This descriptive-comparative study was carried -out on 240 females (each group 120) in Tehran, Iran, by multistage sampling. Data collection tools had 3 parts; General Health Questionnaire (GHQ), demographic variables, and Female Sexual Function Index (FSFI) that were completed by interviews. Descriptive statistics, independent t, Mann-Whitney test, chi-square, and SPPS16 were used for analysis of data. P-values less than 0.05 were considered statistically significant. Results: The difference in sexual function between combined oral contraceptives and cyclofem was insignificant. Scores of desire and arousal dimensions were better in combined oral contraceptive consumers than cyclofem users. Conclusions: It is important for females to choose hormonal contraception methods, which are the most effective, yet, cause the least sexual dysfunction.